Chagas disease - related educational intervention in medical science students - Miguel Alejandro Reyes-Ávila; César Ramón Góngora-Ávila; Samaris María Tamayo-García; Yoeisy Isidro Peña-Peña; Yoandro Larduet-López (Gaceta Médica Estudiantil, 2022)
Introduction: Chagas disease has ceased as a public health problem only for Latin America to become a disease of worldwide relevance. Cuba shows favorable conditions for proliferation of the disease, so, a high level of knowledge concerning this disease it would be successful to prevent the spread of the disease.